(untitled) (Eurasian Journal of Learning and Academic Teaching, 2026)
This article examines the life, multifaceted scientific heritage, and socio-political environment of the prominent 12th-century polymath, Fakhr al-Din al-Razi. Living in an era marked by the decline of the Abbasid Caliphate, the rise of the Mongol threat, and intense sectarian conflicts involving the Batiniyya and Mu’tazilite movements, Al-Razi emerged as a pivotal figure in Islamic intellectual history. The study analyzes his "Razian synthesis"—the integration of Aristotelian logic into Ash’ari theology—and explores how his works in linguistics, physics, and metaphysics provided a resilient framework for the survival of the "rational sciences" (al-ulum al-aqliyya) during political decay. The research concludes that Al-Razi’s methodological innovations acted as an intellectual bridge, ensuring the continuity of the Islamic scholarly tradition into the post-classical era